Pengaruh Pembelajaran Kewirausahaan dan Motivasi Berwirausaha terhadap Minat Berwirausaha Mahasiswa Pendidikan Ekonomi Universitas Jember - Taskiyyah Himma; Retna Ngesti Sedyat; Hetty Mustika Ani (Jurnal Pendidikan Ekonomi Undiksha, 2026)
This study aims to analyze the influence of entrepreneurship learning and entrepreneurial motivation on the entrepreneurial interest of students of Economics Education, University of Jember. The study used a quantitative method with a correlational approach to 203 students selected from a population of 414 students from the 2021–2023 intake through a proportional random sampling technique. Data were collected through questionnaires, interviews, and documentation, then analyzed using multiple linear regression with the help of IBM SPSS 25. The results showed that entrepreneurship learning and entrepreneurial motivation had a positive and significant effect on students' entrepreneurial interest, both partially and simultaneously. The results of the descriptive analysis showed that learning tools, need for achievement, and interest had high values in influencing entrepreneurial interest. The coefficient of determination (R²) value of 0.706 indicates that 70.6% of entrepreneurial interest is influenced by entrepreneurship learning and entrepreneurial motivation, while the remaining 29.4% is influenced by other factors such as ability, feelings of enjoyment, family environment, and community environment.